Analisis Penerapan Akuntansi Syariah Enterprise Theory Pada Lembaga Amil Zakat (Studi Pada Lembaga Amil Zakat (LAZ) Al-Hijrah Medan) - Rahmadani, Suci (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine the application of zakat, infaq and alms accounting in the financial statements of the Al-Hijrah Medan Amil Zakat Institution (LAZ) and to determine the appropriateness of the application of Enterprise Thoery Islamic Accounting in these financial statements. Research Methods on the analysis of the application of Islamic accounting at the Al-Hijrah Al-Hijrah Institute (LAZ) Medan is a study that uses this type of qualitative research. This research method is a study that often refers to the use of qualitative data in the form of interviews, observation and documentation. Qualitative research is research that uses the question and answer method to obtain certain information as desired. The results of the study concluded that the accounting recording process carried out at LAZ Al - Hijrah originated from transaction evidence obtained from the activities of collecting, distributing and utilizing zakat, infaq and alms funds. LAZ Al - Hijrah uses a cash basis recording system and conducts journaling by applying double entry recording. Overall LAZ Al - Hijrah has not implemented Islamic enterprise theory accounting practices in its financial reports. Financial reports that are made are only in the form of a report on the recapitulation of fundraising and a report on the distribution of funds